Русские говоры Терского берега Белого моря: первые результаты и перспективы исследования(Russian Dialects of the Ter Coast of the White Sea: the First Results and Perspectives for the Future) - Lönngren, Tamara (Poljarnyj vestnik, 2011)
The aim of this article is to present the first results of a dialectological expedition undertaken by undergraduate and postgraduate students from the University of Tromsø to the Ter Coast of the White Sea. The paper presents some historical and ethnographical facts from two small villages, Varzuga and Umba. The people in these villages speak Pomor dialects which are poorly investigated but interesting from several points of view. This paper focuses on the lexicon of these Russian dialects. The body of dialectal words and expressions still in use reflects the habits and traditions of the countryside and preserves features of the old folk culture.
Keywords: Russian; langauge; dialectology; Ter coast White Sea